Glyphosate and phosphate treatments in soil differentially affect crop microbiomes depending on species, tissue and growth stage - Smolander, Niina; Fuchs, Benjamin; Helander, Marjo; Puigbo, Pere; Tamminen, Manu; Saikkonen, Kari; Mathew, Suni Anie (NATURE PORTFOLIO, 2025)
Glyphosate-based herbicides (GBHs) are widely used for controlling weeds by inhibiting the shikimate pathway. However, the effects of GBH on non-target organisms, such as shikimate pathway-containing microbes, are understudied. Furthermore, the complex interactions between GBH and fertilizers are difficult to predict. Hence, we experimentally investigated the effects of GBH and phosphate fertilizer on the composition of endophytic bacterial communities of potato, faba bean and oat during early and late summer using 16S rRNA gene sequencing, and on plant growth in late summer. GBH treatments significantly affected bacterial communities of early and late summer potato roots and late summer faba bean roots, while phosphate treatments significantly affected bacterial communities of late summer potato leaves, tubers and early summer faba bean leaves. The treatments reduced bacterial diversity in potato and oat and the abundance of putatively beneficial bacteria in potato and faba bean. However, these treatments increased the aboveground biomass of all crops. Thus, agrochemicals had variable effects across crops, tissues and growth stages. While improved crop yield is often prioritized in chemical-intensive farming, the effects of microbiome shifts on crop health need further investigation.